Experimental study on shear resistance of IMS prestressed friction joints with alveolar surfaces. (November 2022) - Chen, Hongyu; Zhu, Hongguang; Kang, Xiandong; Wang, Fei; Zhao, Zhijian; Liang, Shibo; Yang, Yaowen
Abstract: The integral prefabricated prestressed slab-column structure is called "IMS" system for short. Despite extensive studies on flat IMS structural joints, limited attention has been given to the cogging structure of the contact surface between composite beams and precast columns. Accordingly, an IMS joint with cogging is proposed in this paper. In the joint, the traditional fine aggregate concrete is replaced by a high-strength non-shrinkage steel fiber grouting material. The effects of shear span ratio on the crack development and failure mode of IMS friction joints were experimentally studied using eight full-scale specimens of IMS side joints with different cogging structures. The test results showed that the shear span ratio had a significant influence on the failure mode of the IMS cogged beam-column joint. When the shear span ratio was less than 0.3, the cogging failed in shear; this failure mode played an essential role in the shear resistance of the IMS joint. The setting of the cogging increased the ultimate bearing capacity of the joint by approximately 26.84%. When the shear span ratio exceeded 1.5, the failure mode shifted to the flexural failure of the precast beam. A calculation formula is proposed to estimate the shear capacity of an IMS cogged beam–column joint by considering the structural form of the cogged joint, effective prestress, and shear span ratio. The results given by the calculation formula compared with the experimental results are within the safety margin. The formula shows its potential in practical applications and may be used as a reference for engineering design.